2015
DOI: 10.1007/s12325-015-0185-5
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Ivabradine to β-Blocker Improves Exercise Capacity in Systolic Heart Failure Patients in a Prospective, Open-Label Study

Abstract: Adding ivabradine to carvedilol in patients with chronic heart failure improves the uptitration of β-blocker. The results merit further verification in a prospective double-blind study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 25 publications
4
36
0
2
Order By: Relevance
“…Although HR during exercise was not assessed in this study, ivabradine is also reported to reduce HR during exercise and to improve exercise tolerance. 29 In the present study, the reduction in resting HR was similar among the final doses of ivabradine ranging from 2.5 to 7.5 mg BID (15.2-17.0 beats/min). These findings suggest that the range of appropriate dose adjustment for Japanese HF patients is similar to that for non-Japanese patients (ie, 2.5-7.5 mg BID).…”
Section: Discussionsupporting
confidence: 70%
“…Although HR during exercise was not assessed in this study, ivabradine is also reported to reduce HR during exercise and to improve exercise tolerance. 29 In the present study, the reduction in resting HR was similar among the final doses of ivabradine ranging from 2.5 to 7.5 mg BID (15.2-17.0 beats/min). These findings suggest that the range of appropriate dose adjustment for Japanese HF patients is similar to that for non-Japanese patients (ie, 2.5-7.5 mg BID).…”
Section: Discussionsupporting
confidence: 70%
“…[21,22] Carvedilol and bisoprolol have consistently been shown to be inferior to ivabradine in their effects on symptomatic improvement and on exercise capacity in separate well sized studies. [23,24] Therefore, despite their prognostic benefits beta-blockers do not improve symptoms and functional tolerance in patients with heart failure, but other treatments may do so. Higher doses of betablockers are associated with fatigue and with reduced exercise tolerance and therefore it is unlikely that merely increasing the dose of beta-blockade will improve functional capacity in HF patients.…”
Section: Beta-blockersmentioning
confidence: 99%
“…A further study showed a similar effect with ivabradine added to carvedilol being more effective than uptitrating the dose of cavedilol in patients with HFrEF ( Figure 5). [23] In another large randomised study Volterrani et al compared the effect of heart rate reduction with carvedilol, ivabradine, and their combination on exercise capacity in patients with HFrEF receiving maximal dose of ACE inhibitors. [24] The maximal dose of study treatment was more frequently tolerated in patients receiving ivabradine than in those receiving carvedilol.…”
Section: Ivabradinementioning
confidence: 99%
“…The addition of ivabradine to carvedilol in 69 patients in sinus rhythm, ischaemic HF (NYHA class II-III) and HR ≥70 beats per minute (bpm) revealed a shorter beta-blocker up-titration period, higher final beta-blocker dose as well as greater heart rate reduction and better exercise capacity. 20 …”
Section: Functional Improvement and Symptoms Reliefmentioning
confidence: 99%